Use of letermovir‐valganciclovir combination as a step‐down treatment after foscarnet for ganciclovir‐resistant CMV infection in kidney transplant recipients. Issue 11 (28th October 2021) - Rho, Elena; Näf, Bettina; Müller, Thomas F; Wüthrich, Rudolf P; Schachter, Thomas; von Moos, Seraina
Abstract: Background: Letermovir (LTV) might be an alternative treatment to nephrotoxic foscarnet (FOS) in Ganciclovir (GCV) resistant cytomegalovirus (CMV) infection. However, its efficacy in controlling active CMV viremia is unclear, as it is only approved for CMV prophylaxis in hematopoietic stem‐cell transplantation. Methods: This case series describes 14 kidney transplant recipients (KTR) with moderate‐level GCV resistant CMV infection, treated by different step‐down strategies after initial FOS therapy: (1) Observation without antiviral follow‐up or switch to valganciclovir (VGCV) (pre‐LTV era), and (2) Switch to LTV±VGCV (LTV era). Results: One patient died under FOS. Thirteen patients were followed under step‐down regimens. All but two patients had ongoing CMV viremia when stopping FOS. In pre‐LTV era, 5/9 (56%) experienced a CMV breakthrough > 10 000 IU/ml calling for another course of FOS, as compared to 1/4 (25%) in the LTV era. Addition of VGCV to LTV at low‐level viral breakthrough, addressing a possible developing resistance against LTV, prevented viral surge in two patients. In the pre‐LTV era, CMV‐related death or graft loss occurred in three of nine (33%), compared to no death or graft loss in the LTV era. Conclusion: A step‐down strategy combining LTV+VGCV, might allow to safely stop FOS at ongoing low‐level viremia.